SELECTIVE ELECTROCHEMICAL RECOGNITION OF THE POTASSIUM GUEST CATION IN THE PRESENCE OF SODIUM AND MAGNESIUM-IONS BY A NEW FERROCENYL IONOPHORE - Beer, P; Sikanyika, H; Blackburn, C; Mcaleer, J (1989)
The new ferrocenyl ionophore (6) selectively complexes, electrochemically recognises, and responds to the potassium guest cation in the presence of equimolar amounts of sodium and magnesium ions.